Analisis Pengaruh Pemberian MgSO4 pada Ibu Bersalin Preeklampsia Berat di Fasilitas Kesehatan Pra Rujukan RSUD Jombang terhadap Prevalensi Kejadian Eklampsia - Grah Prihartanti, Niken; Hayu Lestari, Rini; Paramitha Bherty, Chanda (Program Studi S1 Kebidanan - Fakultas Sains dan Kesehatan Universitas PGRI Adi Buana Surabaya, 2021)
In Indonesia, eclampsia is a major cause of maternal death. Eclampsia can be prevented by administering MgSO4 immediately after the diagnosis of severe preeclampsia. However, there are still pre-referral health facilities that do not provide MgSO4 to severe pre-eclampsia mothers. The purpose of this study was to determine the effect of giving MgSO4 to mothers giving birth with severe preeclampsia at the pre-referral health facility at RSUD Jombang on the prevalence of eclampsia. This study is an analytical study using a retrospective cohort design. Based on the estimated sample, 74 mothers were taken from the total population of 119 mothers. The sampling method used simple random sampling. Test analysis using chi square test and Fisher's exact test. Meanwhile, the chance of exposure to risk factors is assessed using Relative Risk (RR). The results of the analysis prove that 2 = 1.014; p = 0.000 which means that there is an effect of MgSO4 on the prevalence of preeclampsia. The results of further analysis obtained a relative risk value (RR) of 1.03, which means that the risk of eclampsia was 1.03 times greater in the group that was not given MgSO4 pre-referral at the site than the mother who was given MgSO4. The conclusion obtained in this study is that there is an effect of giving MgSO4 to mothers giving birth with severe pre-eclampsia at the pre-referral PONEK RSUD Jombang on the occurrence of eclampsia.